2010
DOI: 10.1111/j.1863-2378.2009.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Cessation ofTrichinella spiralisTransmission Among Scavenging Mammals After the Removal of Infected Pigs From a Poorly Managed Farm: Implications for Trichinae Transmission in the US

Abstract: Pigs infected with the zoonotic parasite Trichinella spiralis were detected on a farm in Maryland during an animal welfare investigation. Sera and/or tissues were collected from 49 pigs and three pig carcasses (7 weeks of age to adult, mixed sex). The tissues were tested for the presence of T. spiralis muscle larvae (ML) by tissue digestion, and the sera were tested for the presence of anti-Trichinella antibodies by ELISA. Seventeen of 50 (34%) pigs were infected with T. spiralis based on tissue digestion. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…insectivores and rodents, in the transmission cycle. If we exclude rats where their function in the domestic cycle has been investigated (Schad et al, 1987;Stojcevic et al, 2004;Pozio and Murrell, 2006;Hill et al, 2010), very limited information dating back 50 years is available on Trichinella spp. in insectivores and rodents in the wild (Rausch, 1970).…”
Section: Future Challenges With Trichinella Epidemiologymentioning
confidence: 99%
“…insectivores and rodents, in the transmission cycle. If we exclude rats where their function in the domestic cycle has been investigated (Schad et al, 1987;Stojcevic et al, 2004;Pozio and Murrell, 2006;Hill et al, 2010), very limited information dating back 50 years is available on Trichinella spp. in insectivores and rodents in the wild (Rausch, 1970).…”
Section: Future Challenges With Trichinella Epidemiologymentioning
confidence: 99%
“…It is sporadically reported in free-ranging pigs and poorly managed domestic swine in the US [ 18 , 26 ]. Trichinella spiralis spills over into wildlife when there is a current or historic occurrence of the parasite in pigs [ 18 , 27 , 28 ]. For example, on a poorly managed pig farm in Maryland, the overall prevalence of T. spiralis in adjacent raccoon and opossum populations was 41% (7 of 17) 6 months after pigs had been depopulated from the farm [ 27 ].The prevalence of T. spiralis dropped to 10% (1 of 10) one year after pigs were depopulated and was undetectable (0 of 15) in wild scavengers 18 months after pigs were removed from the farm [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trichinella spiralis spills over into wildlife when there is a current or historic occurrence of the parasite in pigs [ 18 , 27 , 28 ]. For example, on a poorly managed pig farm in Maryland, the overall prevalence of T. spiralis in adjacent raccoon and opossum populations was 41% (7 of 17) 6 months after pigs had been depopulated from the farm [ 27 ].The prevalence of T. spiralis dropped to 10% (1 of 10) one year after pigs were depopulated and was undetectable (0 of 15) in wild scavengers 18 months after pigs were removed from the farm [ 27 ]. A study conducted in 1993 demonstrated that 0.3% (4 of 1294) of domestic and 2.8% (5 of 179) of wild pigs in Florida had anti- Trichinella IgG in their sera [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some preventative strategies for parasitic infections such as Trichinella and T. solium are improved living conditions by better sanitation, education and commercial pig production, regular monitoring and mandatory reporting for the pathogen (Nockler and Kapel 2007;Community E 2005), strict regulations in pig-farms and slaughterhouses (Gottstein et al 2009), adequate vaccination of pigs, health education and human mass chemotherapy (Gottstein et al 2009), pig corralling, and regulations for processing pork and pork products (Garcia et al 2007;Hill et al 2010). However, these preventative practices are not implemented in high-risk countries such as Eastern Europe, Asia, parts of South America and in the African subcontinent.…”
Section: Taenia (T Solium)mentioning
confidence: 99%